Performance of new Hevea clones from IAC 400 series Perfomance de novos clones de Hevea da série IAC 400 - Paulo de Souza Gonçalves; Marcelo de Almeida Silva; Adriano Tosoni da Eira Aguiar; Maria Alice Martins; Erivaldo José Scaloppi Junior; Lígia Regina Lima Gouvêa (Scientia Agricola, 2007)
The Hevea breeding program of Instituto Agronômico de Campinas (IAC) has completed clonal evaluation on the following series: IAC 100, IAC 200 and IAC 300. The performance of 22 clones of Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell.-Arg., evolved at IAC, over a period of eleven years was evaluated in the Western Central part of the São Paulo State, Brazil. Among these 22 new clones, six were intraspecific hybrid clones (IAC 400, IAC 404, IAC 405, IAC 406, IAC 410, IAC 412) and the remaining are primary those resulted from selected ortets within half-sib progenies. An old popular clone RRIM 600, of Malaysian origin, was used as the control. The trial was laid out in a randomized block design with three replications. Yield performance over a period of four years, mean girth at the 11th year, girth increment before tapping and on tapping, thermal property of natural rubber produced, bark thickness, number of latex vessel rows in seven year virgin bark, percentage incidence of tapping panel dryness, wind damage and diseases like leaf and panel anthracnose have been observed. Sixty one percent of the clones were superior in relation to the control for yield. The clone IAC 400 recorded the highest yield (97.40 g tree-1 tap-1) over four years of tapping, followed by IAC 411 (78.87 tree-1 tap-1), whereas the control clone RRIM 600 recorded 50.86 g tree-1 tap-1. All selected clones were vigorous in growth. Girth increment of these clones was average to above average. Except for IAC 423, other clones had thick virgin bark at opening ranging from 4.84 mm for IAC 401 to 6.38 mm for IAC 416. The natural rubbers from IAC clones have shown good thermal stability up to 300ºC and no differences in the thermal behavior among rubber from clones of the IAC series and the clone RRIM 600 were found in inert atmosphere. O programa de melhoramento de Hevea do Instituto Agronômico de Campinas (IAC) completou a avaliação dos clones da série IAC 100, IAC 200 e IAC 300. O desempenho médio em torno de 22 clones de [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell.-Arg.], desenvolvidos pelo IAC, por um período de 11 anos foi avaliado na região Centro Oeste do estado de São Paulo. Dentre os 22 novos clones, seis são resultantes de hibridação intraespecífica (IAC 400, IAC 404, IAC 405, IAC 406, IAC 410, IAC 412) e o restante, clones primários resultantes de ortetes selecionados dentro de progênies de meios irmãos. O clone RRIM 600, de origem Malaia, foi usado como testemunha. O experimento foi conduzido sob delineamento de blocos ao acaso com três repetições. Desempenho da produção sob o período de quatro anos, média do perímetro do caule no décimo primeiro ano, incremento médio anual do perímetro antes e durante a sangria, espessura de casca, número de anéis de vasos laticíferos no sétimo ano de casca virgem, análise por termogravimetria da borracha produzida, percentagem de incidência de seca do painel de sangria, danos causados pelo vento e doenças como antracnose do painel e das folhas foram observados. A maioria dos clones foi superior em produção em relação ao clone RRIM 600. O clone IAC 400 registrou a mais alta produção (97,40 g árvore-1 sangria-1) em quatro anos de sangria o qual foi seguido pelo IAC 411 (78,87 g árvore-1 sangria-1) visto que o clone testemunha registrou 50,36 g árvore-1 sangria-1. Todos os clones selecionados tiveram crescimento vigoroso. Incrementos do perímetro do caule estiveram acima da média. Exceto o IAC 423, outros clones apresentaram espessura de casca virgem na abertura do painel (mm) variando de 4.84mm (IAC 401) a 6.38 mm (IAC 416). As borrachas estudadas apresentaram boa estabilidade térmica até cerca de 300ºC e não foram observadas diferenças no comportamento térmico entre as amostras dos clones da série IAC e as do clone RRIM 600.